Design tools for analog and digital ICs. - Geppert, L. (IEEE spectrum)
The era of the system on a chip is well under way, bringing in its train new headaches for the IC design engineer. One reason for the difficulties is that such systems are increasingly being built up from an assembly of pre-designed components-so-called intellectual property (IP) or virtual components-which sometimes come from diverse sources. Further, a decision is often demanded very early in the design process as to which functions will be executed in hardware and which in software, after which concurrent design of both components is necessary to ensure they work together. Then, too, the shrinking dimensions of the structures that make up the chip are compelling consideration of their physical and electrical properties in much more detail than ever before. All the while, market pressures are forcing companies to design and verify application-specific ICs with millions of logic gates in less and less time